Catalytic peroxynitrite decomposition improves reperfusion injury after heart transplantation - Szabó, Gábor; Loganathan, Sivakkanan; Karck, Matthias; Radovits, Tamás (The journal of thoracic and cardiovascular surgery, 2012)
Objective - Peroxynitrite, a reactive nitrogen species, has been implicated in the development of ischemia-reperfusion injury. The present study investigated the effects of the potent peroxynitrite decomposition catalyst FP15 on myocardial and endothelial function after hypothermic ischemia-reperfusion in a heterotopic rat heart transplantation model. - Methods - After a 1-hour ischemic preservation and implantation of donor hearts, reperfusion was started after application of vehicle (5% glucose solution) or FP15 (0.3 mg/kg). The assessment of left ventricular pressure-volume relations, total coronary blood flow, endothelial function, immunohistochemical markers of nitro-oxidative stress, and myocardial high-energy phosphates was performed at 1 and 24 hours of reperfusion. - Results - After 1 hour of reperfusion, myocardial contractility (maximal slope of systolic pressure increment at 140 μL left ventricular volume: 5435 ± 508 mm Hg/s vs 2346 ± 263 mm Hg/s), coronary blood flow (3.98 ± 0.33 mL/min/g vs 2.74 ± 0.29 mL/min/g), and endothelial function were significantly improved, nitro-oxidative stress was reduced, and myocardial high-energy phosphate content was preserved in the FP15-treated animals compared with controls. - Conclusions - Pharmacologic peroxynitrite decomposition reduces reperfusion injury after heart transplantation as the result of reduction of nitro-oxidative stress and prevention of energy depletion and exerts a beneficial effect against reperfusion-induced graft cardiac and coronary endothelial dysfunction.
Available online 6 March 2012
Gesehen am 22.06.2018